Inhibitory efficacy of eugenol purified from volatile oil of clove flowers against some bacterial isolates contaminated with minced meat. (Journal of the College of Basic Education, 2022)
The research included conducting a qualitative detection of the active groups in the volatile oil of clove flowers obtained from the National Center for Medicinal Herbs, and the results showed the presence of all active groups except glycosides and coumarins. The initial detection was carried out on the volatile oil compounds using the thin layer chromatography (TLC) technique, and the flow rate (RF) was 0.59 and equal to the standard model for comparison. ), the result showed the presence of the eugenol compound with a retention time of 11.517, while the retention time of the standard eugenol sample was 11.373, which indicates the purity of the extracted model.